2016
DOI: 10.1186/s12876-016-0551-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of liver transplantation in patients with hepatitis C infection are not affected by HCV positivity of a donor

Abstract: BackgroundThe use of HCV-positive livers for HCV-positive recipients is becoming more common. Our aim is to evaluate long-term outcomes in liver transplant recipients transplanted with HCV antibody-positive organs.MethodsFrom the Scientific Registry of Transplant Recipients (1995–2013), we selected all adult liver transplant recipients with HCV, and cross-sectionally compared long-term graft loss and mortality rates between those who were transplanted from HCV antibody-positive (HCV+) vs. HCV antibody-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Recently, Durand et al have also reported equally good longterm patient survival between recipients of overdose drug donors compared with both trauma and medical death donors. Similarly, longterm outcomes of recipients of an HCV positive liver transplantation with organs from HCV‐positive donors are similar to those of HCV‐negative recipients based on a recent Scientific Registry of Transplant Recipients analysis, indicating equally good outcomes regardless of the viral status of the donor . We found a significant improvement in the likelihood of organ acceptance when we informed patients that the risk of contracting HIV/HCV is lower than the risk from many daily activities and that the transplanted IRD organ may be of a significantly better quality, may be transplanted sooner, and may lead to a similar outcome as transplantation with a non‐IRD organ.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, Durand et al have also reported equally good longterm patient survival between recipients of overdose drug donors compared with both trauma and medical death donors. Similarly, longterm outcomes of recipients of an HCV positive liver transplantation with organs from HCV‐positive donors are similar to those of HCV‐negative recipients based on a recent Scientific Registry of Transplant Recipients analysis, indicating equally good outcomes regardless of the viral status of the donor . We found a significant improvement in the likelihood of organ acceptance when we informed patients that the risk of contracting HIV/HCV is lower than the risk from many daily activities and that the transplanted IRD organ may be of a significantly better quality, may be transplanted sooner, and may lead to a similar outcome as transplantation with a non‐IRD organ.…”
Section: Discussionsupporting
confidence: 69%
“…The poor efficacy of HCV treatments prior to the DAA era translated to graft injury and loss or recurrent cirrhosis. In the pre‐DAA era, mortality in HCV patients transplanted from HCV‐positive donors has been shown to be 12.5% at 1 year, 24.2% at 3 years, and 33.0% at 5 years, with a graft loss rate of 2.2% at 1 year, 4.8% at 3 years, and 7.5% at 5 years with no difference noted in those transplanted with HCV‐negative donors . Conversely, although access to medication remained a problem, in the DAA era HCV‐positive liver transplant recipients have had improved early graft survival compared with those treated in the pre‐DAA era .…”
Section: Discussionmentioning
confidence: 99%
“…In kidney recipients, the risk of having received an HCV‐positive kidney translated to a 1% lower survival at 1 year and a 2% lower survival at 3 years, while the benefits to patients were potentially significant, as HCV‐positive recipients who underwent transplantation with HCV‐positive kidneys spent over a year less time on the waiting list than those HCV‐positive recipients who waited for HCV‐negative kidneys at the same transplant center . Liver recipient's mortality and graft loss at 1, 3, and 5 years was not significantly different in the HCV‐positive liver recipients of HCV‐positive or HCV‐negative donors …”
Section: Hepatitis C Virusmentioning
confidence: 98%
“…It is well recognized that utilization of HCV organs is lower than that of HCV‐negative organs . The argument that many have made is that this is due to the lack of acceptable HCV‐positive recipients.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
See 1 more Smart Citation